Composites Based Green Poly(L-Lactic Acid) and Dioctyl Phthalate: Preparation and Performance - Yan-Hua Cai; Li-Sha Zhao; Yan-Hua Zhang (Advances in Materials Science and Engineering)
The effects of dioctyl phthalate (DOP) on performances of poly(L-lactic acid) (PLLA) were investigated in detail using optical depolarizer, X-ray diffraction, melt index instrument, and electronic tensile tester. Crystallization performance showed that the half time of overall PLLA crystallization t1/2 decreased with increasing of crystallization temperature (80°C to 105°C), but the t1/2 of PLLA/DOP composites firstly decreased and then increased, and t1/2 of PLLA/DOP exhibited minimum value at 85°C. Compared to neat PLLA, 20%DOP made the t1/2 decrease from 7258.3 s to 265.4 s. X-ray diffraction experiment further confirmed that DOP could accelerate the crystallization of PLLA. The fluidity of PLLA/DOP composites indicated that the melt mass flow rate firstly decreased and then greatly increased with increasing of DOP content. The mechanical performance showed that DOP could improve the general mechanical performance, and the elongation at break of PLLA/25%DOP was about 30 times longer than that of neat PLLA.